Experiences of the Patients with Behcet's Syndrom from Adherence to Treatment: A Qualitative Content Analysis - Narjes Taheri; Camellia Torabizadeh; Elham Aflaki; Mehdi Mohammadi; Zahra Khademian (Shiraz University of Medical Sciences, 2021)
Background: Adherence to treatment plays an important role in the effectiveness of treatment in patients with Behcet's Syndrome (BS). An in-depth understanding of the experiences of patients with BS will help to improve the patients' management. The present qualitative study aimed to explore the experiences of patients with BS from adherence to treatment. Methods: This qualitative study was conducted during February-September 2019 at Shahid Motahari Behcet's Clinic in Shiraz, Iran. Data were collected through eight unstructured observations and 22 individual in-depth semi-structured interviews with 20 participants (15 patients with BS, three family members, and two rheumatologists). Data analysis was performed simultaneously with data collection, using the conventional content analysis as proposed by Graneheim and Lundman. Data were managed using MAXQDA 10 software. Results: Data analysis resulted in 21 sub-categories, seven categories, and three themes. The themes included barriers to treatment adherence (inability to cope with treatment and challenges in access to health care), facilitators of treatment adherence (incentives, receiving support, and striving to adapt to illness), and missing aspects of the treatment program (inadequate patient education and the neglect of lifestyle modification). Conclusion: The barriers to and facilitators of treatment adherence as well as the missing aspects of the treatment program of patients with BS were identified. Adherence to treatment is not only determined by the patients, but also affected by the support system and relies upon the existing context and the nature of the treatment plan. These parameters should be considered during patient management to effectively promote treatment adherence.